2020
DOI: 10.1155/2020/7403034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous versus Topical Tranexamic Acid in Nondeformity Spine Surgery: A Meta-Analysis

Abstract: Objective. Tranexamic acid (TXA), an antifibrinolytic agent, interferes with fibrinolysis and has been used for many years to reduce blood loss during spine surgery. The purpose of our meta-analysis was to compare the effect of intravenous versus topical administration of TXA in patients undergoing nondeformity spine surgery. Methods. We searched multiple databases, including PubMed, Embase, the Cochrane library, CNKI, WanFang database, and VIP to find studies that met the inclusion criteria. A meta-analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A plethora of studies has demonstrated TXA's effects in reducing blood loss and transfusion rates. 5 Although most studies focused on the intravenous and topical forms of TXA, 8,16 this is one of the first studies in the spine literature that compares IV versus PO formulations of TXA. We found no difference in the efficacy between the two routes of administration in both the primary outcome of hemoglobin drop and secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies has demonstrated TXA's effects in reducing blood loss and transfusion rates. 5 Although most studies focused on the intravenous and topical forms of TXA, 8,16 this is one of the first studies in the spine literature that compares IV versus PO formulations of TXA. We found no difference in the efficacy between the two routes of administration in both the primary outcome of hemoglobin drop and secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the pooled analysis showed that the significant effect of reducing perioperative blood loss and blood transfusion rate might make TXA the drug of choice. TXA, as an antifibrinolytic drug, is currently mainly used in orthopedic, cardiac, and spine surgery to treat or prevent excessive perioperative blood loss [ 6 ]. TXA was administered through a variety of routes, including IV, topical, and oral.…”
Section: Discussionmentioning
confidence: 99%
“…TXA, a synthetic lysine analogue, exerts an antifibrinolytic effect through binding to the lysine-binding sites on plasminogen molecules and inhibiting fibrinolysis [ 6 ]. Some clinical studies and meta-analyses show that intravenous (IV) TXA can reduce blood loss and allogeneic blood transfusion without the high risk of complications such as pulmonary embolism (PE), deep vein thrombosis (DVT), or other [ 1 5 , 7 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity was investigated by using the Q test and the I 2 test. The values of I 2 25%-50%, 50%-75%, and >75% were considered as low, moderate, and high heterogeneity, respectively [ 13 ]. We perform the random-effects model when I 2 > 50% and P < 0.1.…”
Section: Methodsmentioning
confidence: 99%